2021
DOI: 10.2967/jnmt.121.263081
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling99mTc-Pertechnetate Thyroid Uptake: Statistical, Machine Learning, and Deep Learning Approaches

Abstract: Although reference ranges for 99m Tc thyroid percentage uptake vary, the seemingly intuitive evaluation of thyroid function does not reflect the complexity of thyroid pathology and biochemical status. The emergence of artificial intelligence in nuclear medicine has driven problem solving associated with logic and reasoning, warranting reexamination of established benchmarks in thyroid functional assessment. Methods: This retrospective study of 123 patients compared scintigraphic findings with grounded truth es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In D (normal 18 F-DCFPyL PET), ChatGPT highlighted areas that show low uptake in truth (“bright”) incorrectly as “potential areas of increased uptake” (red circles added by ChatGPT). The images were modified from research that was originally published in J Nucl Med, as cited in 9,11,16,17 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In D (normal 18 F-DCFPyL PET), ChatGPT highlighted areas that show low uptake in truth (“bright”) incorrectly as “potential areas of increased uptake” (red circles added by ChatGPT). The images were modified from research that was originally published in J Nucl Med, as cited in 9,11,16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…In D (normal 18 F-DCFPyL PET), ChatGPT highlighted areas that show low uptake in truth ("bright") incorrectly as "potential areas of increased uptake" (red circles added by ChatGPT). The images were modified from research that was originally published in J Nucl Med, as cited in 9,11,16,17 The number of cases with committing answers (ie, specific answer in relation to the image) and, among them, appropriate answers is shown for both versions of ChatGPT (percentage relative to the total of 15 cases). errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1643 articles were extrapolated with the computer literature search and, by reviewing the titles and abstracts, 1627 of them were excluded because the reported data were not within the field of interest of this review. Sixteen articles were therefore selected and retrieved in full-text version [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and one additional study was also found screening the references of these articles (Fig. 1) [34]; as a consequence, the total number of studies evaluated in the review was 17.…”
Section: Literature Searchmentioning
confidence: 99%
“…DL architecture to produce fourth‐order radiomic features from thyroid images. Image reprinted with permission Currie and Iqbal 2022 17 …”
Section: Deep Radiomicsmentioning
confidence: 99%